Role of Caesium in Higher Alcohol Synthesis over Modified Copper–Cobalt Nanocomposites under Mild Conditions. Issue 10 (2nd May 2017) - Das, Subhasis; Sengupta, Manideepa; Bordoloi, Ankur
Abstract: Cu–Co nanocomposites with and without Cs promoter on a modified lanthanum–alumina support were prepared by the combination of two unique synthesis methods. The synthesized materials were exclusively characterized by means of XRD, BET surface area determination, H2 temperature‐programmed reduction, CO2 temperature‐programmed desorption, N2 O frontal chromatography, X‐ray photoelectron spectroscopy, high‐resolution TEM, and elemental mapping techniques, and its catalytic properties were thoroughly investigated for the selective synthesis of higher alcohols in the CO hydrogenation reaction by using a H2 /CO ratio of 1, a temperature range of 180–300 °C and a pressure variation of 15–60 bar. Cs incorporation and a Cu/Co ratio of three was found to be a very efficient combination to obtain alcohol selectivities up to 55 %. This was explained by the fact that Cs increases the surface area of Cu particles by migrating Cu towards the surface layer and strengthens the surface interaction of Cu and Co. The further increase in higher alcohols selectivity then results from the limited formation of methane and carbon dioxide. Abstract : Three is a magic number : Caesium‐promoted and unpromoted copper–cobalt catalysts are tested in the CO hydrogenation reaction for selective higher alcohol synthesis. The presence of caesium, an electronic promoter, enhances the selectivity to higher alcohols to 55 % at mild reaction conditions.